2010
DOI: 10.1007/s00431-010-1310-8
|View full text |Cite
|
Sign up to set email alerts
|

Early intravenous immunoglobin (two-dose regimen) in the management of severe Rh hemolytic disease of newborn—a prospective randomized controlled trial

Abstract: Phototherapy is the standard treatment in moderately severe hemolytic disease of newborn (HDN), whereas exchange transfusion (ET) is the second line in progressive cases. Intravenous immunoglobin (IVIG) has been suggested to decrease the need for ET. We aimed at assessing the efficacy of early two-dose regimens of IVIG to avoid unnecessary ET in severe Rh HDN. The study included 90 full-term neonates with Rh incompatibility unmodified by antenatal treatment and not eligible for early ET and which were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…Alpay et al [12] showed that, high dose of IVIG (1 g/ kg) reduces hemolysis, serum bilirubin levels and risk of exchange transfusion in rhesus and ABO hemolytic disease on the other hand; Girish et al [13] demonstrated that, low dose of IVIG (0.5 g/kg) was also found to be as efficacious as high dose IVIG in reducing the duration of phototherapy. However low dose IVIG found to be less effective in avoiding exchange transfusion in rhesus hemolytic disease of the newborn [14]. Apart from these results, SmitsWintjen concluded that prophylactic treatment with IVIG in rhesus hemolytic disease did not reduce the need for exchange transfusion or adverse neonatal outcomes [15].…”
Section: Resultsmentioning
confidence: 99%
“…Alpay et al [12] showed that, high dose of IVIG (1 g/ kg) reduces hemolysis, serum bilirubin levels and risk of exchange transfusion in rhesus and ABO hemolytic disease on the other hand; Girish et al [13] demonstrated that, low dose of IVIG (0.5 g/kg) was also found to be as efficacious as high dose IVIG in reducing the duration of phototherapy. However low dose IVIG found to be less effective in avoiding exchange transfusion in rhesus hemolytic disease of the newborn [14]. Apart from these results, SmitsWintjen concluded that prophylactic treatment with IVIG in rhesus hemolytic disease did not reduce the need for exchange transfusion or adverse neonatal outcomes [15].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 included studies, 7 evaluated neonates with only Rh isoimmunisation,8 10 12 24 25 34 35 2 assessed neonates with only ABO isoimmunisation13 36 and 3 enrolled neonates with both Rh and ABO isoimmunisation 9 11 33. Most of the RCTs included a study population of term neonates.…”
Section: Resultsmentioning
confidence: 99%
“…Although exchange transfusion is a critical therapy for prevention of kernicterus in neonates with rapidly rising bilirubin, it does have complications 28 . IVIg has been shown to reduce the need for exchange transfusion in some studies 29,30 . However, it does not affect anemia significantly, and top off transfusions may still be needed…”
Section: Diagnosis and Treatmentmentioning
confidence: 98%